2007
DOI: 10.1021/jo702088c
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of TBD-Catalyzed Ring-Opening Polymerization of Cyclic Esters

Abstract: Triazabicyclodecene (TBD) has recently been shown to be an effective organocatalyst for the ring-opening polymerization (ROP) of cyclic esters. Using DFT methods, we have studied possible mechanisms of this reaction. Our studies explain not only the narrow polydispersity index (PDI) observed in the ROP of six-membered ring lactones, but also the surprising failure of the ROP for the more reactive butyrolactone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
144
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 27 publications
9
144
0
1
Order By: Relevance
“…The TBD catalyst offered a fast reaction under mild conditions, potentially conferring advantages over Sn(Oct)2 which has been extensively used in ROP previously. [43][44][45] The DSC data demonstrated that the alkyl side chains of ε-DL disrupted the packing in the PεDL block compared to PCL blocks, generating mPEG-b-PεDL micelles with amorphous cores. The finding that PεDL homopolymer was amorphous was also supported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The TBD catalyst offered a fast reaction under mild conditions, potentially conferring advantages over Sn(Oct)2 which has been extensively used in ROP previously. [43][44][45] The DSC data demonstrated that the alkyl side chains of ε-DL disrupted the packing in the PεDL block compared to PCL blocks, generating mPEG-b-PεDL micelles with amorphous cores. The finding that PεDL homopolymer was amorphous was also supported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from DSC measurements of CLPSQ1, LAPSQ, COPSQs, and poly(LA) containing no PSQ structure were exhibited in Figure 4. The melting point, T m , of poly(CL) has been reported to be around 60 C. 21 On the other hand, poly(LA) shows the endotherm due to T m over 150 C. [23][24][25][26] In the thermogram of CLPSQ1, the melting endotherm was observed at 53.8 C. However, no endotherm peak over 150 C was found in the case of LAPSQ. The point of inflection in the curve of LAPSQ around 48 C seemed to be T g of poly(LA) chain.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Since, from the mechanistic analysis, the use of 1,5,7-triazabicyclo [4.4.0]dec-7-ene (TBD) catalyst with alcohol or amine as an initiator is reported to enable the living-like polymerization of CL. 20,21 In addition, the procedure is free from the use of metal catalyst, which is sometimes difficult to remove from the product completely. The results of our previous examination demonstrated that the procedure was applicable to the graft ring-opening polymerization of CL from the polysilsesquioxane having phenyl and amino groups (APSQ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the catalytic role of TBD as proton donor and acceptor was highlighted, the activation pathway differs from previous DFT calculations studies involving concerted proton transfer. 29,32,33 In our continuous effort to promote the organocatalytic synthesis of PHUs and to fully understand the origin of the high catalytic activity of TBD organocatalyst, we report a detailed mechanistic study of the guanidine organocatalysed ringopening of propylene carbonate by amines using DFT calculations. In order to highlight the inuence of the amine nucleophilicity, the uncatalysed model reaction between propylene carbonate and aniline, methylamine and cyclohexylamine was rst considered.…”
mentioning
confidence: 99%